Collective Transformations, Collective Theories: What Adult Educators Can Learn from the Boston Women’s Health Book Collective - Susan Birden (Adult Education Research Conference, 2002)
The Boston Women’s Health Book Collective designed and participated in education that was similar in approach and effect to Paulo Freire’s critical pedagogy. As with Freire’s work in Brazil, the women’s process of conscientization went beyond mere intellectual transformation, preparing them to work for dramatic changes in American healthcare.